Prevalence of Undernutrition Among Children and Adolescents with Cancer Living in Sub-Saharan African Countries: A Systematic Review and Meta-analysis - Berhanu Mengistu MSc; Aysheshim Kassahun Belew MSc; Lemlem Daniel Baffa MPH; Elsa Awoke Fentie MPH; Muluken Chanie Agimas MPH; Ever Siyoum Shewarega MPH; Esmael Ali Muhammed MSc; Mekuriaw Nibret Aweke MPH (Global Pediatric Health)
Objective . To systematically review studies to provide the pooled estimate of undernutrition among children and adolescents with cancer living in sub-Saharan African countries. Methods . The review followed the recommendations outlined in the PRISMA statement. Online searches were performed on electronic databases such as PubMed, Scopus, Embase, and Hinari; gray literature sources: such as Google, Google Scholar, and university repositories were also searched. A random effect model was used to drive the pooled prevalence, and was reported at a 95% Confidence Interval (CI). Heterogeneity was assessed using subgroup analysis and univariable meta-regression. The effect of each study on the overall prevalence was assessed using leave-one-out sensitivity analysis. In all the models, statistical significance was set at P -value <.05. Result . A total of 623 articles were identified, and 21 articles were retrieved for the final analysis. The overall pooled prevalence of undernutrition was 41.34% (95% CI: 31.64%, 51.04%). The highest prevalence of undernutrition was observed from studies that used Arm Muscle Area (AMC) for age to assess undernutrition: 61.66% (95% CI: 47.59%, 75.72%). The protocol for this review has been registered at PROSPERO (CRD42024510052). Conclusion . The prevalence of undernutrition in sub-Saharan African countries was considerably high. Therefore, policy directions and cost-effective approaches that sustainably address undernutrition among pediatric patients with cancers are needed.